Ibu Bijak, Keuangan Cermat: Edukasi Pengelolaan Keuangan Keluarga Berbasis Literasi Finansial - Kartika Ayu Kinanti; Yulian Ade Chandra; Ayu Nareswari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Effective household financial management is a key factor in maintaining family well-being. However, many housewives still face challenges in managing their finances due to limited knowledge of budgeting, saving habits, and basic investment concepts. This low level of financial literacy can increase the risk of household economic instability, especially amid continuously changing economic conditions. To address this issue, this community service program was implemented to provide practical and applicable financial literacy education tailored to the needs of housewives. The program was delivered through interactive training sessions, offering participants a better understanding of financial literacy fundamentals, realistic household budgeting techniques, basic saving and investment strategies, and ways to avoid harmful debt practices. Through this training, participants are expected to gain the skills and confidence needed to apply sound financial principles in their daily lives. The expected outcomes of this activity include improved financial literacy among participants, the ability to independently create structured household financial plans, and positive changes in financial behavior that promote responsibility and discipline. Furthermore, the program aims to raise awareness of the importance of financial planning as a foundation for a more stable and prosperous family future.